2013
DOI: 10.1007/s00018-013-1534-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of dendritic cell homeostasis and function: lessons from cell type-specific gene ablation

Abstract: Dendritic cells (DCs) are a heterogeneous cell population of great importance in the immune system. The emergence of new genetic technology utilizing the CD11c promoter and Cre recombinase has facilitated the dissection of functional significance and molecular regulation of DCs in immune responses and homeostasis in vivo. For the first time, this strategy allows observation of the effects of DC-specific gene deletion on immune system function in an intact organism. In this review, we present the latest finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 116 publications
(151 reference statements)
1
4
0
Order By: Relevance
“…Note that by crossing the parental Cre-expressing lines with Rosa26-ZsGreen reporter mice (Madisen et al, 2010) the resultant mice showed specific recombination in most hepatocytes (identified by morphology), and liver fibroblast (GFP + /PDGFRβ + ), with about 98.2 ± 0.72% hepatic stellate cells that co-expressed GFP + and PDGFRβ + signals (Fig S5E,F). Similarly, hepatic DCs (GFP + /CD11c + ) had 94.17 ± 2.16% colocalization with GFP, while the colocalization percentage of F4/80 + KCs or LCMs (GFP + /F4/80 + ) was 78.14 ± 5.03% (Fig S5E ,F) (Bleriot & Ginhoux, 2019;Karmaus & Chi, 2014;Madisen et al, 2010). is smaller than their own (12 ± 0.1 µm), similar to what we previously reported (Catarinella et al, 2016).…”
Section: Hecs Mediate the Anti-metastatic Activity Of Ifnαsupporting
confidence: 88%
“…Note that by crossing the parental Cre-expressing lines with Rosa26-ZsGreen reporter mice (Madisen et al, 2010) the resultant mice showed specific recombination in most hepatocytes (identified by morphology), and liver fibroblast (GFP + /PDGFRβ + ), with about 98.2 ± 0.72% hepatic stellate cells that co-expressed GFP + and PDGFRβ + signals (Fig S5E,F). Similarly, hepatic DCs (GFP + /CD11c + ) had 94.17 ± 2.16% colocalization with GFP, while the colocalization percentage of F4/80 + KCs or LCMs (GFP + /F4/80 + ) was 78.14 ± 5.03% (Fig S5E ,F) (Bleriot & Ginhoux, 2019;Karmaus & Chi, 2014;Madisen et al, 2010). is smaller than their own (12 ± 0.1 µm), similar to what we previously reported (Catarinella et al, 2016).…”
Section: Hecs Mediate the Anti-metastatic Activity Of Ifnαsupporting
confidence: 88%
“…To gain insights into the role of SIRT1 in DCs, we generated a CD11c with CD11c-Cre (referred to as SIRT1 CD11c−/− hereafter). In addition to DCs, the expression of CD11c in monocytes/macrophages, neutrophils, and some B cells has also been reported (29,30). To examine the specificity and efficacy of SIRT1 deletion, we isolated various cell populations (indicated in SI Appendix, Fig.…”
Section: The Differentiation Of Naive Cd4mentioning
confidence: 99%
“…Note that by crossing the parental Cre-expressing lines with Rosa26-ZsGreen reporter mice ( Madisen et al, 2010 ) the resultant mice showed specific recombination in most hepatocytes (identified by morphology), and liver fibroblast (GFP + /PDGFRβ + ), with about 98.2 ± 0.72% hepatic stellate cells that co-expressed GFP + and PDGFRβ + signals ( Figure 4—figure supplement 1E, F ). Similarly, hepatic DCs (GFP + /CD11c + ) had 94.17 ± 2.16% colocalization with GFP, while the colocalization percentage of F4/80 + KCs or LCMs (GFP + /F4/80 + ) was 78.14 ± 5.03% ( Figure 4—figure supplement 1E,F ; Blériot and Ginhoux, 2019 ; Karmaus and Chi, 2014 ; Madisen et al, 2010 ). Finally, HECs, including LSECs, (GFP + /CD31 + ) showed 85.3 ± 5.03% colocalization ( Figure 4—figure supplement 1E, F ), with no expression of GFP signals in cells other than CD31 + .…”
Section: Resultsmentioning
confidence: 88%